Acetylcholine in irritable bowel syndrome pathogenesis and the role of cholineblockers - Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate value of disorders of cholinergic innervation in pathogenesis of irritable bowel syndrome (IBS).Original positions. The important place in regulation of gastro-intestinal tract functions belongs not only to M-, but also to N-receptors localized in enteral plexus ganglions and on presynaptic endings of cholinergic motor neurones. Acetylcholine is the universal mediator which is intimately interacts with other mediators regulating intestinal functions. The role of disorders of cholinergic innervation in pathogenesis of IBS is actively investigated by now. Experimental data allow to assume, that «subclinical inflammation» within intestinal wall at IBS, disturbances of peristaltic activity and hyperalgesia, are related to altered response of immune and smooth-muscle cells to acetylcholine stimulation.Conclusion. Acetylcholine represents the major mediator regulating motor and secretory function of intestine. Change of acetylcholine metabolism of has immediate value in pathogenesis of IBS. The agents, influencing cholinergic receptors, are one of basic resources of modern pharmaceutical therapy of irritable bowel syndrome.